Consumption of dairy products and prevalence of depression and anxiety among adults - Maryam Mofidi-Nejad; Alireza Milajerdi; Ammar Hassanzadeh Keshteli; Hamid Afshar; Peyman Adibi; Alireza Khadem (Journal of Health, Population and Nutrition)
Abstract Background No earlier study has examined the association between dairy intake and prevalence of depression and anxiety in Middle Eastern population. Objective This cross-sectional study was done to investigate the association between consumption of total dairy intake and prevalence of depression and anxiety in a large group of adult population in Isfahan, Iran. Methods Dairy intake was assessed for 3362 participants using a validated 106-item Willet-format dish-based semi-quantitative FFQ. A validated questionnaire of Hospital Anxiety and Depression Scale was used to examine depression and anxiety. We defined scores of > 8 as depressed and anxious people in this analysis. Information about covariates were collected using pre-tested questionnaires. Results Mean age of study population was 36.2, 58.3% of them were females. Participants in the highest quintile of dairy intake had a 40% lower chance for depression compared to those in the lowest quintile (OR = 0.60; 95%CI 0.47–0.76, Ptrend = 0.001) in crude model. This association remained significant after controlling for several confounders (0.57; 95%CI 0.40–0.80 Ptrend = 0.02). Although we observed a significant association between dairy intake and anxiety in crude model (OR: 0.63; 95%CI 0.46–0.87, Ptrend = 0.02), the association was not significant when we took into account potential confounders (0.63; 95%CI 0.39–1.00). Conclusion We found an inverse association between consumption of dairy products and depression but the results for anxiety were not significant. Further studies, in particular of prospective nature, are recommended to confirm our findings.